Comparative effectiveness of Pilates and yoga group exercise interventions for chronic mechanical neck pain: quasi-randomised parallel controlled study. Issue 3 (September 2016) - Dunleavy, K.; Kava, K.; Goldberg, A.; Malek, M.H.; Talley, S.A.; Tutag-Lehr, V.; Hildreth, J.
Abstract: Objectives: To determine the effectiveness of Pilates and yoga group exercise interventions for individuals with chronic neck pain (CNP). Design: Quasi-randomised parallel controlled study. Setting: Community, university and private practice settings in four locations. Participants: Fifty-six individuals with CNP scoring ≥3/10 on the numeric pain rating scale for >3 months (controls n = 17, Pilates n = 20, yoga n = 19). Interventions: Exercise participants completed 12 small-group sessions with modifications and progressions supervised by a physiotherapist. Main outcome measures: The primary outcome measure was the Neck Disability Index (NDI). Secondary outcomes were pain ratings, range of movement and postural measurements collected at baseline, 6 weeks and 12 weeks. Follow-up was performed 6 weeks after completion of the exercise classes (Week 18). Results: NDI decreased significantly in the Pilates baseline: 11.1 [standard deviation (SD) 4.3] vs Week 12: 6.8 (SD 4.3); mean difference −4.3 (95% confidence interval −1.64 to −6.7); P < 0.001 and yoga groups [baseline: 12.8 (SD 7.4) vs Week 12: 8.1 (SD 5.6); mean difference −4.7 (95% confidence interval −2.1 to −7.4); P < 0.00], with no change in the control group. Pain ratings also improved significantly. Moderate-to-large effect sizes (0.7 to 1.8) and low numbers needed to treat were found. There were no differences in outcomes between the exercise groups or associated adverse effects. No improvements in range of movement or posture were found. Conclusions: Pilates and yoga group exercise interventions with appropriate modifications and supervision were safe and equally effective for decreasing disability and pain compared with the control group for individuals with mild-to-moderate CNP. Physiotherapists may consider including these approaches in a plan of care. Clinical Trial Registration Number: ClinicalTrials.govNCT01999283 .